Penerapan Pola Asuh Anak Usia Dini di TK Aisyah 2 Desa Cijulang Kecamatan Cijulang Kabupaten Pangandaran - Pitriani, Hani; Farha Nayli Syafa’ah; Ayi Nurajijah; Neneng Nurlaelatul Musyarofah; Arlan Hidayatulloh; Kiki Prima Rizky; Yayat Hidayat; Dasep Ubaedilah (PT. ALHAFI BERKAH INDONESIA, 2024)
Parenting is a process of guiding, educating and disciplining carried out by parents towards children to achieve independence and shape children's behavior by applying certain norms that exist in the family and society. Aisyiyah 2 Kindergarten students were the objects of research regarding parenting patterns for early childhood. From the results that can be seen, there are some parents who do not pay attention to good parenting patterns, so that children do not become what they want. Therefore, researchers held a seminar related to parenting patterns for early childhood at Kindergarten Aisyiyah 2. The aim of this research was to provide understanding and knowledge to parents of Kindergarten Aisyiyah 2 students regarding parenting patterns for early childhood. The technique in this research is observation, interview and documentation methods. In this case, researchers participated in the learning process at Kindergarten Aisyiyah 2 in order to find out how children with appropriate parenting styles differ from those who do not. The research results show that appropriate parenting is one of the factors that influences character formation in children for the future.